The Perfekt theory of M-ideals - Werner, Dirk (MATHEMATICA SCANDINAVICA, 2022)
We revisit some ideas of K.-M. Perfekt who has provided an elegant framework to detect the biduality between function or sequence spaces defined in terms of some o- respectively O-condition. We present new proofs under somewhat weaker assumptions than before and apply the result to Lipschitz spaces.